1992
DOI: 10.3109/00016349209021052
|View full text |Cite
|
Sign up to set email alerts
|

Medical termination of early pregnancy with mifepristone (RU 486) followed by a prostaglandin analogue: Study in 16, 369 women

Abstract: We report the results of a large-scale trial with mifepristone (RU 486) followed by the administration of a prostaglandin (PG) analogue for the medical termination of early pregnancy. Altogether, 16,173 patients from 300 centers were evaluated. 48 women (0.3%) were lost to follow-up prior to, and 416 (2.6%) after the PG administration, and therefore the efficacy was evaluated in 15,709 women. Overall, the success rate was 95.3%, with no statistical difference regarding the nature and dose of PG used. The media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
1
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(73 citation statements)
references
References 11 publications
2
66
1
4
Order By: Relevance
“…Also, the data collected on 16 000 women who had been treated with 600 mg of mifepristone followed by a prostaglandin analogue 24-72 hours later suggested that the efficacy was highest if the interval was 48 hours. 9 Different time intervals between mifepristone and misoprostol have also been tested 10 or both drugs have been administered simultaneously, 11 repeating the dose of misoprostol if abortion was not complete. When misoprostol was not repeated, complete abortion rates seem to be significantly lower with shorter intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the data collected on 16 000 women who had been treated with 600 mg of mifepristone followed by a prostaglandin analogue 24-72 hours later suggested that the efficacy was highest if the interval was 48 hours. 9 Different time intervals between mifepristone and misoprostol have also been tested 10 or both drugs have been administered simultaneously, 11 repeating the dose of misoprostol if abortion was not complete. When misoprostol was not repeated, complete abortion rates seem to be significantly lower with shorter intervals.…”
Section: Introductionmentioning
confidence: 99%
“…PGs and TXs play ubiquitous and vital pathophysiological and therapeutic roles in human health and disease states, such as glaucoma: pregnancy, labor, delivery; and abortion: gastric protection and peptic ulcer formation; intestinal fluid secretion; liver protection and damage; airway resistance and asthma; blood pressure control; and modulation of inflammatory cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In our study there was 88%rate of complete abortion &12% needed surgical evacuation or a second dose of misoprostol. Ulmann, A., Silvestre, L., Chemama et al report a large-scale trial with mifepristone (RU 486) followed by the administration of a prostaglandin with a overall success rate 95.3% irrespective of dose and route of administration of drugs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies over the last decade focused on safety, efficacy, dosage and medical squeal of abortion with the mifepristone-prostaglandin-protocol, conclude that it is a safe and effective protocol for medical termination, with a wide acceptability and a better alternative to surgical abortions [3,6]. The present study was designed to understand why women resort to M.A., what social, psychological, economical reasons drive them to take the step instead of using a reliable contraception to prevent such a predicament-which is much easier-.…”
Section: Introductionmentioning
confidence: 99%